Multimodal and palliative treatment of patients with pulmonary metastases - Baldes, Natalie (J Thorac Dis, 2021)
Pulmonary metastasectomy has become an important part of the multimodality treatment. Surgical practice is based on observational studies published during the last decades, since no randomized clinical trials exist on the topic. However, the overall survival can be improved after pulmonary metastasectomy in carefully selected patients. The objective of resection of pulmonary metastases is to remove all tumor while preserving as much normal pulmonary parenchyma as possible and reduce invasiveness. Contrary, nonsurgical local treatment options for pulmonary metastases include thermal ablation techniques and stereotactic ablative body radiation. Thermal ablation techniques include microwave, cryotherapy and radiofrequency ablation. The present review article gives an overview on the topic and should help thoracic surgeons to make the right decisions in their daily practice.